Induced pluripotent stem cells: new possibilities in neurobiology and neurotransplantaion - O. S. Lebedeva; M. A. Lagarkova; S. N. Illarioshkin; L. G. Khaspekov; I. A. Grivennikov (Анналы клинической и экспериментальной неврологии, 2017)
The discovery of embryonic stem cells (ES) and methods of EShandling belong to most significant achievements of science inthe 20th century. As mammalian ES represent an essentiallyunlimited source of non-differentiated cells with normal diploidcaryotype, they will remain to be an important object in basicresearch, including neurobiology, although their use for the purposesof practical neurology meets a number of medical andethical difficulties. Results of last studies open completely newpossibilities in the field of cell therapy of severe human disorders.We are talking about reprogramming of somatic cells in mammalians,including humans, into pluripotent stem cells (so calledinduced pluripotent stem cells, iPS), with their furtherdifferentiation to cells of different types. The practical capabilityof patients iPS to be transformed into dopaminergic andother specific neurons of the CNS is shown, that gives to doctorsa fundamentally new technology of getting adequate and geneticallyidentical cell material for neurotransplantation inParkinsons disease, Huntingtons disease and other severe neurodegenerativedisorders.